In Hospital Outcomes of Combined Coronary Artery Bypass Grafting (CABG) and Carotid Endarterectomy (CEA) - Bakhsh, Allah; Paras, Iftikhar; Hussain, Ghulam; Moeen, Muhammad; Ahmad, Nisar; Ahmad, Naseem; Baig, Mirza Ahmad Raza (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine the early outcomes of surgery in patients who underwent CABG plus CEA and those in whom carotids left untreated in patients having concomitant coronary artery plus carotid artery disease. METHODOLOGY: In this retrospective comparative analysis, we included 60 patients of severe coronary and carotid artery disease, 30 patients who underwent concomitant CABG plus CEA surgery and others who underwent only CABG and no CEA in spite of having severe carotid artery disease. All CEA patients were asymptomatic. These patients were operated from 1-Dec-2010 to 31-Dec-2015. Incidence of stroke and mortality were the primary study outcomes. RESULTS: Mean age of patients in CABG+CEA group was 55.24+6.89 versus 57.53+9.42 years in CABG group. There were 80.0% males in CABG+CEA group and 73.3% in CABG group. 66.7% patients in CABG+CEA group were hypertensive and there were 63.3% hypertensive patients in CABG group. In patients of CABG+CEA, total 2 (6.6%) patients died. One patient died on operation day when he was on ventilator. His brain could not be assessed. One patient had stroke on opposite side of CEA. Doppler study showed stenosis of CEA graft, so its graft was revised. This patient expired after one week. In patients of CABG only, stroke occurred in one patient and that patients died on 5th operative day. CONCLUSION: In present study, cerebral morbidity was little high in CABG+CEA patients but with in-significant statistical difference. There is no benefit of prophylactic CEA in cardiac surgery patients having severe asymptomatic carotid artery disease.